Revisiting the ESG–Firm Value Nexus: The Mediating Role of Intellectual Capital in Indonesia's Energy Sector - Ni Nyoman Putu Martini; Diyah Probowulan; Norita Citra Yuliarti; Rai Rake Setyawan (The Indonesian Accounting Review, 2026)
This study examines the relationship between ESG disclosure, intellectual capital (IC), and firm value in Indonesia's energy sector, analyzing 34 companies listed on the Indonesia Stock Exchange (2022–2024). Four hypotheses were tested: (1) ESG's effect on firm value, (2) ESG's effect on IC, (3) IC's effect on firm value, and (4) IC's mediating role in the ESG–firm value link. Using GRI standards for ESG disclosure, VAIC as an IC proxy, and PBV/Tobin's Q for firm value, the study applied PLS-SEM via SmartPLS 4. Results revealed that ESG and IC together explained only 2.9% of firm value variation (R² = 0.029), with all path coefficients statistically insignificant at the 5% level. Specifically, ESG had a negligible negative effect on firm value (β = −0.123, p = 0.159) and IC (β = −0.006, p = 0.926), while IC's impact on firm value was also insignificant (β = 0.116, p = 0.166). The indirect effect of ESG on firm value via IC was similarly weak (β = −0.001, p = 0.947). The findings suggest that in Indonesia's energy sector, traditional financial metrics outweigh ESG or IC in driving market valuation. This challenges theoretical frameworks such as stakeholder theory, legitimacy theory, and the resource-based view, indicating their limited applicability in certain institutional and sectoral contexts.